MOF-derived CoNiFe-LDH / CCH self-supporting electrode material and preparation method thereof
By growing nanosheets encapsulating nanoneedles in situ on nickel foam to form a 3D polyhedral CoNiFe-LDH/CCH electrode material, the problems of monotonous morphology and limited electrochemical performance improvement of ternary layered hydroxide materials were solved, achieving high specific capacity and long lifetime electrochemical performance.
Patent Information
- Application Number
- CN202411500985.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-07
AI Technical Summary
Existing ternary layered hydroxide materials have limited morphology, poor adjustability, and limited improvement in electrochemical performance.
Using a MOF-derived CoNiFe-LDH/CCH self-supporting electrode material preparation method, a 3D polyhedral structure of nanosheets encapsulating nanoneedles is grown in situ on nickel foam through hydrothermal, chemical etching and ion exchange steps. Combined with the synergistic effect of multiple metal ions, a high specific surface area and abundant active sites are formed.
The specific capacitance and cycle stability of the electrode material were improved, achieving high conductivity and long repeat life. The specific capacitance reached 2856.6 F/g at a current density of 1 A/g, and it retained 93.02% of the initial capacitance after 3000 cycles.
Smart Images

Figure CN119274988A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of supercapacitor electrode materials, and in particular relates to a MOF-derived CoNiFe-LDH / CCH self-supporting electrode material and a preparation method thereof. Background Art
[0002] In order to achieve the dual carbon goals, it is urgent to develop green, efficient and sustainable renewable energy, especially the utilization of solar and wind energy, which has promoted the development of efficient electrochemical energy conversion and storage technology. Among them, supercapacitors (SC) have attracted much attention due to their high power output, fast charging and discharging capabilities, long cycle life and environmental protection, and are considered to be an expansion or substitute for power storage systems.
[0003] Layered double hydroxides (LDHs) have attracted much attention due to their high theoretical specific capacitance, abundant sources and environmental friendliness. At present, two or three metal cations are introduced between the LDHs layers to form a composite material. Therefore, LDHs show better ion permeability and abundant redox active sites, and are widely used in catalysts and electrode materials. Chinese patent CN114420467A reports "a method for regulating the components of a ternary layered metal hydroxide electrode material". This method first prepares a soluble metal salt and a component regulator into a mixed electrolyte, and then obtains a ternary metal hydroxide electrode material grown in situ on the surface of a conductive substrate by a constant potential deposition method. While maintaining a high specific capacitance, the cycle stability of the electrode is extended to a certain extent. Chinese patent CN114944285A reports that "Urchin-like CoNiFe ternary hydroxide nano-electrode material" uses nickel cobalt iron nitrate as raw material and uses a one-step hydrothermal method to synthesize urchin-like CoNiFe nano-electrode material. The synergistic effect of Ni, Co, and Fe and the unique urchin-like nanostructure make the material have a large specific surface area, so that the active sites of the electrode material participating in the reaction can be fully contacted with the electrolyte, thereby improving the electrochemical performance of the electrode material. The literature (Hierarchical web-like NiFeMn ternary hydroxides microstructure assembled on reduced graphene oxide for binder-free supercapacitorelectrode." Diamond and Related Materials 125 (2022): 109009.) synthesized a trimetallic hydroxide assembled on a rGO membrane by a one-pot two-step hydrothermal method on a nickel foam matrix. The obtained NiFeMn-LDH / rGO has excellent electrochemical properties, such as high surface capacity, long cycle life, and good rate performance.
[0004] As can be seen from the above examples, there are some methods for preparing ternary layered hydroxides and composite materials, but most of these methods are prepared in one pot by mixing three soluble metal salts. The resulting materials have a single morphology, poor adjustability, and active substances are easy to aggregate. The electrochemical performance still needs to be further improved. Summary of the invention
[0005] In order to overcome the above technical problems existing in the prior art, the purpose of the present invention is to provide a MOF-derived CoNiFe-LDH / CCH self-supporting electrode material and a preparation method and application thereof.
[0006] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is as follows: The first aspect of the present invention provides a method for preparing a MOF-derived CoNiFe-LDH / CCH self-supporting electrode material, comprising the following steps: (1) Pretreating a nickel foam (NF) substrate; dissolving cobalt salt and urea in deionized water to obtain a cobalt salt solution; (2) The pretreated NF was placed in a polytetrafluoroethylene-lined reactor, and the above-mentioned cobalt salt solution was poured into it. After hydrothermal reaction for 8-12 h, it was taken out and washed and dried to obtain (1D) nanoneedles of basic cobalt carbonate (Co(CO3)) grown on nickel foam. 0.5 (OH)•0.11H2O), abbreviated as CCH; (3) soaking the CCH obtained in step (2) in a 2-methylimidazole solution, ultrasonicating at room temperature for 15-30 min, standing, washing and drying to obtain a ZIF-67 / CCH precursor; the 2-methylimidazole solution is obtained by dissolving dimethylimidazole and hexamethylenetetramine in a mixed solution of anhydrous ethanol and deionized water; (4) soaking the ZIF-67 / CCH precursor in an ethanol solution of nickel salt, standing, washing and drying to obtain NiCo-LDH / CCH; (5) The NiCo-LDH / CCH was immersed in an aqueous solution of an iron (II) salt, and then washed and dried after standing to obtain a CoNiFe-LDH / CCH self-supporting electrode material.
[0007] Furthermore, in step (1), the NF substrate pretreatment method is: first, NF (10 cm × 10 cm × 0.1 cm) is cut into a size of 1 × 3 cm, and then the NF is placed in 3M hydrochloric acid, acetone, anhydrous ethanol and deionized water for ultrasonic pretreatment for 30 min, the ultrasonic frequency is 20-40kHz, and then taken out and placed in a vacuum drying oven at 60-80°C for 7-9h to obtain the pretreated NF.
[0008] Furthermore, in step (1), the molar ratio of the cobalt salt to urea is 1:2, and the molar concentration of cobalt in the cobalt salt solution is 0.2 mol / L. The cobalt salt is cobalt nitrate hexahydrate.
[0009] Furthermore, in step (2), the hydrothermal reaction temperature is 100-140°C.
[0010] Furthermore, in the dimethylimidazole solution of step (3), the molar ratio of dimethylimidazole to hexamethylenetetramine is 10-12:1, the concentration of dimethylimidazole is 1-1.2 mol / L, and the volume ratio of deionized water to anhydrous ethanol is 1:1.
[0011] Furthermore, in step (3), the ultrasonic frequency is 20-40 kHz and the standing time is 12-14 h.
[0012] Furthermore, in step (4), the nickel salt ethanol solution has a nickel molar concentration of 0.04 mol / L. The nickel salt is nickel nitrate hexahydrate.
[0013] Furthermore, in step (5), the aqueous solution of the iron (II) salt has a molar concentration of 0.02-0.06 mol / L. The iron (II) salt is ferrous sulfate heptahydrate.
[0014] Furthermore, the standing time in steps (4) and (5) is 1-3 h.
[0015] The washing and drying described in the above technical scheme are both washing with anhydrous ethanol and deionized water in sequence and then drying in a vacuum drying oven at 60°C-80°C for 8-12 hours.
[0016] The second aspect of the present invention provides a MOF-derived CoNiFe-LDH / CCH self-supporting electrode material prepared by the above-mentioned preparation method, wherein the overall structure thereof contains a 3D polyhedral structure supported by nanosheets wrapped in nanoneedles, which effectively increases the specific surface area of the material and can provide more active sites.
[0017] The third aspect of the present invention provides the use of the above-mentioned MOF-derived CoNiFe-LDH / CCH material as an electrode material in a supercapacitor.
[0018] The above-mentioned MOF-derived CoNiFe-LDH / CCH material is directly generated on nickel foam, and the electrochemical performance can be directly tested without the need for conductive agent and adhesive treatment. The electrochemical performance test is carried out using a three-electrode system, such as using CoNiFe-LDH / CCH as the working electrode, platinum mesh as the counter electrode, Hg / HgO electrode as the reference electrode, and 3 mol / L KOH as the electrolyte. The CoNiFe-LDH / CCH electrode material prepared under the optimal conditions has a specific capacitance of 2856.6 F / g at a current density of 1 A / g, and after 3000 cycles of charge and discharge, the sample can maintain 93.02% of its initial capacitance.
[0019] The technical principles and beneficial effects of the present invention are as follows: The present invention uses porous conductive metal NF as a carrier, adopts a hydrothermal process to prepare basic cobalt carbonate with compact nano needles, uses this as a sacrificial template to induce the in-situ growth of ZIF-67, and combines the auxiliary additive hexamethylenetetramine control strategy to prepare a self-supporting ZIF-67 active material with a high load. Therefore, CCH plays a key role in inducing the in-situ growth of ZIF-67. Then, a CoNiFe ternary electrode material with a multidimensional structure is prepared in situ by chemical etching and ion exchange methods. The chemical etching and ion exchange methods can provide more active sites required for redox, so that it has a higher specific capacity.
[0020] The present invention adopts one-step hydrothermal, chemical etching and ion exchange methods to prepare a CoNiFe-LDH / CCH electrode material that does not require bonding with a binder. The technical solution does not require complex equipment, has low material cost and is simple to operate.
[0021] The MOF-derived CoNiFe-LDH / CCH self-supporting electrode material prepared by the present invention has a 3D polyhedral structure in which nanosheets are wrapped around nanoneedles, which effectively increases the specific surface area of the material, provides more active sites, and improves the specific capacity of the electrode material.
[0022] The present invention further dopes Fe on MOF-derived NiCo-LDH / CCH to increase the hydroxide interlayer spacing, effectively induce the disorder of the crystal structure, increase its specific surface area, thereby providing more active sites and better conductivity, and improving the charge transfer efficiency. At the same time, due to the synergistic effect of the three metal ions, it has abundant electrochemical active sites and more redox reaction electron pairs, so that its specific capacity is higher, and it maintains a stable structure during multiple constant current charge and discharge processes, and can be recycled multiple times.
[0023] The CoNiFe-LDH / CCH binder-free electrode prepared by the present invention exhibits high conductivity and long repeated cycle life without peeling stability, and the charge transfer and diffusion of electrolyte ions in the electrode are more capable than powder electrode materials. When the current density is 1A / g, the specific capacitance can reach 2856.6F / g. After 3000 cycles of charge and discharge, the sample can maintain 93.02% of its initial capacitance and can be used for supercapacitors with high energy density. The present invention is environmentally friendly, has low material cost, excellent electrochemical performance, and has great potential in the practical application of supercapacitors. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 These are SEM images of (a) CCH, (b) ZIF-67 / CCH, (c) NiCo-LDH / CCH, and (d) CoNiFe-LDH / CCH materials prepared in Example 1.
[0025] Figure 2 It is the XRD spectra of CCH, ZIF-67 / CCH, NiCo-LDH / CCH and CoNiFe-LDH / CCH materials prepared in Example 1.
[0026] Figure 3 The samples of Example 1-4 were scanned at a rate of 5 mV·s -1 Cyclic voltammetry curves of the test.
[0027] Figure 4 The sample of Example 1 is 1-9 mV·s -1 Cyclic voltammetry curves.
[0028] Figure 5 It is the constant current charge and discharge curve of the samples of Examples 1-4 tested at a current density of 1 A / g.
[0029] Figure 6 It is the constant current charge and discharge curve of the sample of Example 1 tested at a current density of 1-10 A / g.
[0030] Figure 7 This is the electrochemical impedance spectrum of the sample in Example 1.
[0031] Figure 8 This is the cycle stability diagram of the sample in Example 1. DETAILED DESCRIPTION
[0032] The present invention will be further described in detail below with reference to the accompanying drawings and embodiments, but the present invention is not limited thereto. Example 1
[0033] A MOF-derived CoNiFe-LDH / CCH self-supporting electrode material and a preparation method thereof, comprising the following steps: 1) NF (10 cm × 10 cm × 0.1 cm) was cut into 1 × 3 cm in size, and then NF was ultrasonically pretreated in 3M hydrochloric acid, acetone, anhydrous ethanol and deionized water for 30 min at an ultrasonic frequency of 30 kHz. After being taken out, NF was placed in a vacuum drying oven at 60 °C for 8 h. 2) Dissolve cobalt nitrate hexahydrate (5 mmol, 1.455 g) and urea (10 mmol, 0.6 g) in 25 mL of deionized water and stir at room temperature for 15 min to obtain a plum-red mixed solution; 3) The treated NF substrate was placed in a polytetrafluoroethylene liner, and the mixed solution was poured into the substrate. After hydrothermal reaction at 110°C for 10 h, the substrate was taken out and washed with ethanol and deionized water three times each. After vacuum drying at 60°C for 10 h, CCH was obtained. 4) Dissolve dimethylimidazole (0.82 g, 10 mmol) and hexamethylenetetramine (0.14 g, 1 mmol) in a mixed solution of 5 mL deionized water and 5 mL anhydrous ethanol, and ultrasonicate at room temperature for 15 min at an ultrasonic frequency of 30 kHz. Place CCH in the mixed solution and let stand at room temperature for 12 h. Wash with ethanol and deionized water three times each, and vacuum dry to obtain a ZIF-67 / CCH precursor. 5) Dissolve nickel nitrate hexahydrate (1 mmol, 0.29 g) in 25 mL of ethanol. Place ZIF-67 / CCH in the solution at room temperature for 2 h. Wash with ethanol and deionized water three times each, and vacuum dry at 60 °C for 10 h to obtain NiCo-LDH / CCH; 6) Ferrous sulfate heptahydrate (1 mmol, 0.278 g) was fully dissolved in 25 mL of deionized water. Subsequently, NiCo-LDH / CCH was placed in the solution at room temperature for 2 h. The NiCo-LDH / CCH was washed three times with ethanol and deionized water respectively, and vacuum dried at 60 °C for 10 h to obtain CoNiFe-LDH / CCH.
[0034] The morphology of the products obtained in different steps of Example 1 was characterized by a SUPRA-55 field emission scanning electron microscope produced by Zeiss, Germany, and the phase of the products obtained in different steps of Example 1 was characterized by a D / max2500 X-ray diffractometer produced by Rigaku Corporation, Japan.
[0035] from Figure 1 (a) and (b) show that with the assistance of hexamethylenetetramine, polyhedral ZIF-67 is anchored on the CCH nanoneedles. Figure 1 (c) and (d) it can be seen that the nanosheets uniformly wrap the ZIF-67-derived layered metal hydroxides, and the nanosheets are closely arranged.
[0036] Figure 2 The XRD patterns of the powders formed in different steps in Example 1 are as follows: Figure 2 The characteristic peaks of CCH are shown, which match the crystal plane of the basic cobalt carbonate standard card (PDF#48-0083). The diffraction peak position of ZIF-67 / CCH is composed of CCH and ZIF-67 phases, which is consistent with the SEM image results. After etching, the diffraction peak of ZIF-67 disappears, while the diffraction peak of NiCo-LDH / CCH appears and corresponds to the new diffraction peak of the Ni(OH)2·0.75H2O (PDF#38-0715) standard card, confirming the formation of layered double hydroxide (LDHs) structure. The diffraction peak of CoNiFe-LDH / CCH (003) crystal plane shifts to the left due to the participation of Fe in ion exchange. 3+ It brings more anions into the LDH interlayer spacing, effectively inducing the disorder of the crystal structure and increasing its specific surface area, thereby providing more active sites and better conductivity, and improving the charge transfer efficiency. Example 2
[0037] The difference between this embodiment and embodiment 1 is that the amount of ferrous sulfate heptahydrate used in step 6) is 0 mmol. The other steps and parameters are the same as those in embodiment 1. Example 3
[0038] The difference between this embodiment and embodiment 1 is that the amount of ferrous sulfate heptahydrate used in step 6) is 0.5 mmol. The other steps and parameters are the same as those in embodiment 1. Example 4
[0039] The difference between this embodiment and embodiment 1 is that the amount of ferrous sulfate heptahydrate used in step 6) is 1.5 mmol. The other steps and parameters are the same as those in embodiment 1.
[0040] The electrode materials prepared in Examples 1-4 were subjected to electrochemical performance tests, and the electrolyte used was 3 mol / L KOH to test their electrochemical properties.
[0041] The specific operation is as follows: the test is carried out under a three-electrode system, the materials prepared in Examples 1-4 are used as working electrodes, the counter electrode is a platinum mesh, and the reference electrode is a Hg / HgO electrode, which are placed in a 3 mol / L potassium hydroxide solution through a three-hole electrode holder; a Swiss Metrohm electrochemical workstation (PGSTAT-302N) is used in the Cyclic Voltammetry Potentiostatic mode. Figure 3 The samples of Examples 1-4 were scanned at a rate of 5 mV·s -1It can be seen that the integrated area of the cyclic voltammetry curve of the sample in Example 1 is significantly higher than that of the samples in other examples, indicating that it has a stronger energy storage capacity. Figure 4 The voltage scan rate of the sample in Example 1 was measured in the voltage range of 0-0.6 V to be 1-9 mV·s -1 The cyclic voltammetry curves at 200 ℃ and 800 ℃ show that with the increase of scanning speed, the peak intensity of redox peak gradually increases, and the shape remains stable, indicating that the sample has good capacitance performance. Figure 5 The constant current charge and discharge curves of the samples of Examples 1-4 at a current density of 1 A / g in the Chrono Charge Discharge mode. It can be seen that the sample of Example 1 has the longest discharge time and the highest specific capacity, which is consistent with the cyclic voltammetry test results. Figure 6 The constant current charge-discharge diagrams of the sample of Example 1 at current densities of 1 A / g, 2 A / g, 3 A / g, 5 A / g and 10 A / g were tested. By calculation, at a current density of 1 A / g, the sample had a specific capacitance of 2856.6 F / g, at a current density of 10 A / g, it still had a specific capacitance of 1998.5 F / g, and at a current density of 1 A / g, it still had a specific capacitance of 1998.5 F / g. When increased to 10 A / g, the rate capability is 70.4%; Figure 7 The electrochemical impedance spectrum of sample 1 was measured in the FRA.Impedance Potentiostatic mode. From the impedance diagram, it can be seen that the semicircle diameter of the prepared sample is small, the internal resistance is 0.713 Ω, and it has a faster ion diffusion rate and ultra-low charge transfer resistance in the electrochemical process. Figure 8 This is the cycle performance diagram of the sample in Example 1. It can be seen from the figure that after 3000 charge and discharge cycles, the sample can still maintain 93.02% of its initial capacitance, and can still maintain excellent capacity value after long-term cycling, and can be used as an electrode material in a supercapacitor.
[0042] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a MOF-derived CoNiFe-LDH / CCH self-supporting electrode material, characterized in that: The following steps are involved: (1) Pretreating a nickel foam (NF) substrate; dissolving cobalt salt and urea in deionized water to obtain a cobalt salt solution; (2) placing the pretreated nickel foam in a cobalt salt solution for hydrothermal reaction, washing and drying, to obtain 1D nanoneedle basic cobalt carbonate grown on the nickel foam, abbreviated as CCH; (3) soaking CCH in a 2-methylimidazole solution, ultrasonicating at room temperature for 15-30 min, standing, washing and drying to obtain a ZIF-67 / CCH precursor; the 2-methylimidazole solution is obtained by dissolving dimethylimidazole and hexamethylenetetramine in a mixed solution of anhydrous ethanol and deionized water; (4) soaking the ZIF-67 / CCH precursor in an ethanol solution of nickel salt, standing, washing and drying to obtain NiCo-LDH / CCH; (5) NiCo-LDH / CCH was immersed in an aqueous solution of iron (II) salt, allowed to stand, washed and dried to obtain CoNiFe-LDH / CCH self-supporting electrode material.
2. The method for preparing the CoNiFe-LDH / CCH self-supporting electrode material derived from MOF according to claim 1, characterized in that: In step (1), the molar ratio of the cobalt salt to urea is 1:2, and the molar concentration of cobalt in the cobalt salt solution is 0.2 mol / L.
3. The method for preparing the CoNiFe-LDH / CCH self-supporting electrode material derived from MOF according to claim 1, characterized in that: In step (2), the hydrothermal reaction temperature is 100-140° C., and the hydrothermal reaction time is 8-12 h.
4. The method for preparing the CoNiFe-LDH / CCH self-supporting electrode material derived from MOF according to claim 1, characterized in that: In the dimethylimidazole solution described in step (3), the molar ratio of dimethylimidazole to hexamethylenetetramine is 10-12:1, the concentration of dimethylimidazole is 1-1.2 mol / L, and the volume ratio of deionized water to anhydrous ethanol is 1:
1.
5. The method for preparing the CoNiFe-LDH / CCH self-supporting electrode material derived from MOF according to claim 1, characterized in that: In step (3), the standing time is 12-14 h; and / or the ultrasonic frequency is 20-40 kHz.
6. The method for preparing the CoNiFe-LDH / CCH self-supporting electrode material derived from MOF according to claim 1, characterized in that: In the ethanol solution of the nickel salt, the molar concentration of nickel is 0.04 mol / L.
7. The method for preparing the CoNiFe-LDH / CCH self-supporting electrode material derived from MOF according to claim 1, characterized in that: The aqueous solution of the iron (II) salt has a molar concentration of the iron (II) salt of 0.02-0.06 mol / L.
8. The method for preparing the CoNiFe-LDH / CCH self-supporting electrode material derived from MOF according to claim 1, characterized in that: The iron (II) salt is ferrous sulfate heptahydrate.
9. A MOF-derived CoNiFe-LDH / CCH self-supporting material prepared by the method according to any one of claims 1 to 8.
10. Use of the CoNiFe-LDH / CCH self-supporting material derived from the MOF according to claim 9 as an electrode material in a supercapacitor.
Citation Information
Patent Citations
Component regulation and control method of ternary layered metal hydroxide electrode material
CN114420467A
Sea urchin-shaped CoNiFe ternary hydroxide nano electrode material
CN114944285A
Cited By
Cobalt-iron layered hydroxide and carbon nanotube composite material as well as preparation method and application thereof
CN120866875A
Preparation method of MOF-derived LDH catalyst and application of MOF-derived LDH catalyst in singlet oxygen dominated catalysis
CN122558565A